2014
DOI: 10.1182/asheducation-2014.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic targeting and personalized approaches for AML

Abstract: Acute myeloid leukemia (AML) is a genetically heterogeneous clonal hematopoietic stem cell disorder and the majority of patients with AML die from their disease. The treatment paradigms for AML were developed decades ago and, although there have been improvements in the outcomes of selected younger patients and those with specific cytogenetic and molecular genetic characteristics, the overall survival for older patients remains dismal. Over the last few years, next-generation sequencing technologies have ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…4 ) [ 30 ]. Based on mechanism of action, genes involved in signal transduction ( FLT3 , CSF3R , KIT , NRAS , PTPN11 , CBL and JAK2 ) and DNA methylation ( DNMT3A , TET2 , IDH1 and IDH2 ) were the most frequent mutated groups, accounting for 24 (31 %) and 18 (23 %) out of 77 detectable mutations [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 ) [ 30 ]. Based on mechanism of action, genes involved in signal transduction ( FLT3 , CSF3R , KIT , NRAS , PTPN11 , CBL and JAK2 ) and DNA methylation ( DNMT3A , TET2 , IDH1 and IDH2 ) were the most frequent mutated groups, accounting for 24 (31 %) and 18 (23 %) out of 77 detectable mutations [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings have emphasized the potential of using epigenetically targeted therapies for the treatment of AML. Indeed, the DNMT inhibitors 5-azacitidine and 5-aza-2′deoxycytidine (decitabine) are effective agents in the treatment of patients with myelodysplastic syndromes and AML [13]. …”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate the utility of our method in AML using two independent genome-wide methylation datasets (see Figure 1). AML is the ideal case-study for our methodology, as recent work has shown that the AML epigenome evolves independently of mutational burden, and, furthermore, patients with AML respond well to DNA demethylating agents (also known as "epigenetic drugs") [13][14][15][16] . Using our pipeline, we recover significance for the most commonly used AML medication, cytarabine, as well as three other candidates with ongoing preclinical research in the AML space.…”
Section: Introductionmentioning
confidence: 99%